Sterqulia quadrifida R.Br: A Comprehensive Review of Ethnobotany, Phytochemistry, Pharmacology and Toxicology - Ulfa Afrinurfadhilah Darojati; Retno Murwanti; Triana Hertiani (Universitas Sebelas Maret, 2022)
Sterculia quadrifida, R.Br. is one of the plants that grows on the mainland of Timor, East Nusa Tenggra. Sterculia quadrifida, R.Br. commonly known as Peanut tree in English and faloak in Indonesian has various pharmacological activities and has been widely used in traditional medicine. This review article aimed to provide a comprehensive overview of the potential of the faloak plant as an herbal medicine by looking at various aspects such as ethnobotany, phytochemicals, pharmacology and toxicity. Literature searches are carried out in scientific databases that are accepted worldwide such as ScienceDirect, Scopus, PubMed, Springer Link, Wiley Online Library and advanced searches on Google scholars, books, abstracts, theses, scientific reports, and several non-impact and non-indexed journals with the search keywords